Influência imediata das peças podais das palmilhas posturais sobre a postural corporal, equilíbrio ortostático e distribuição da pressão plantar - Fernandes, Patrícia Guimarães (2017)
Introduction: Several types of insoles are used to promote changes in body positioning and improve balance. The postural insoles are orthoses used to correcting or improving postural alignment, balance and weight bearing. Podal elements are used in this insoles, positioned in specific places to promote this correction. The immediate effects of the elements on posture are factors that define the prescription of the insoles. Objective: To carry out a systematic review of the literature about the effect of insoles on static balance and posture. We verified the immediate effects of the podal elements (infracapital and retrocalcanenus bar, calcaneus wedges and infracuboid element) on a posture, static balance and a weight bearing of healthy individuals. Methodology: The review was implemented in the Medline, PuMed, SciELO and Cochrane Library databases. Inclusion criteria of the studies: interventional studies with insoles, published from 2010 to 2016; measurement of postural variables and static balance; in Portuguese and English. Fifteen studies were selected. The experimental, controlled and randomized study included a sample composed of 60 healthy individuals divided by raffle in control group (30) and study group (30). The inclusion criteria were: individuals between 18 and 40 years of age of both genders without musculoskeletal pain complaints. The exclusion criteria were: reports of injuries or neurological diseases, vertigo or dizziness, pregnant women with spinal or foot surgeries, foot ulcers, amputation, visual impairment, who are using postural insoles, without girdles asymmetries and with discrepancy in the length of the lower limbs greater than 5 millimeters. Postural evaluation and static baropodometry and stabilometry were performed. From the postural changes, the podal elements were prescribed for the study group. Both underwent identical reassessment, in the study group with the elements under the feet. The Shapiro-Wilk normality test (S-W) was used and, from this test, parametric and non-parametric tests were used according to the variable. For the analysis of the posture the chi square test was used and for comparative analysis of baropodometry and stabilometry the Wilcoxon test was performed. Results: In the systematic review, we did not find a positive result of insoles on the posture, but the results indicated an improvement of the static balance with the use of insoles in individuals who already presented balance deficit. In the clinical trial, pelvic and scapular assimetries improved and the plantar pressure peak decreased (p <0.05). Conclusion: Although the results point to an improvement in the static balance, due to the wide variety of insoles and populations studied, it was not possible to establish a consensus in the systematic review. In the experimental study, the podal elements were able to improve the posture and distribution of plantar pressure. Positive effects on balance in normal subjects not be proved in this research, which may be due to the time of exposure to the stimulus and also to the characteristics of the sample.